Perencanaan Pengembangan Pembangkit Sistem Muna-Buton dengan Mempertimbangkan Sistem Interkoneksi - Ahmad Fatana; Sarjiya; Lesnanto Multa Putranto (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2022)
Electrical energy consumption has increased annually. It is in line with the fulfillment of electricity sales for the last five years (2013-2017) with a 5.1% growth per year. Muna and Buton are large islands in Southeast Sulawesi with a population of 360,682 and an area of 7,712.18 km2. Muna and Buton are two main cities in Southeast Sulawesi that are developing rapidly. Those two regions are relatively rich in natural potential, promoting local economic growth. The primary source of electricity for both regions is Buton. Current electricity consumption in Muna and Buton is relatively high, with a peak load of 37 MW primarily fulfilled by diesel power plants (pembangkit listrik tenaga diesel, PLTD) of 30.15 MW. The government's target to achieve a new renewable energy mix (NRE) of 23% in 2025 and 31% in 2050 is contrary to the situation of generations in Muna and Buton, which is currently still dominated by PLTD. The planning was conducted by looking at its effect on the cost of generation construction, reserve margin, energy mix, and total cost. The desired optimization value was achieved through several performed scenarios, i.e., an isolated or pre-interconnection scenario, assuming each system was separated, and an interconnection system, assuming that interconnection was performed in Muna and Buton system. The optimization method was carried out using mixed-integer linear programming (MILP) by employing the OSeMOSYS software platform. The optimization results show that the Muna-Buton generation expansion planning has been successfully carried out. Of the several performed scenarios, the scenario with the interconnection system can be selected as the best option. It is based on the total cost value and reduced generation costs of 1,073 IDR per kWh in 2022 and 1,362 IDR per kWh in 2047, with an average of 1,202 IDR per kWh.